2019
DOI: 10.1016/j.jsames.2019.102325
|View full text |Cite
|
Sign up to set email alerts
|

Digital outcrop modelling using “structure-from- motion” photogrammetry: Acquisition strategies, validation and interpretations to different sedimentary environments

Abstract: Structure from Motion-Multi-View Stereo (SfM-MVS) is a relatively new technique that is being adopted in the analysis of sedimentary systems. The technique is especially applicable to studies which focus on the distribution, geometry and quantification of geological bodies including the analysis of sedimentary forms and tectonic structures. This photogrammetric method allows for generating virtual outcrops (VO) and high-resolution digital terrain models (DTMs). In comparison with more sophisticated and expensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 75 publications
1
13
0
4
Order By: Relevance
“…A field campaign was carried out in 2011, and living microbial mats were identified and sampled for the first time in several ponds of the Maquinchao Riverbed [35]. Successive field campaigns (i.e., in 2015-2018 revealed that the ponds containing microbial mats had dried out completely ( Figure 1A,B), and the water level of Carri Laufquen Grande had undergone fluctuations [36]. However, several mineralized microbial mats were preserved on hard substrates mostly of basaltic composition.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A field campaign was carried out in 2011, and living microbial mats were identified and sampled for the first time in several ponds of the Maquinchao Riverbed [35]. Successive field campaigns (i.e., in 2015-2018 revealed that the ponds containing microbial mats had dried out completely ( Figure 1A,B), and the water level of Carri Laufquen Grande had undergone fluctuations [36]. However, several mineralized microbial mats were preserved on hard substrates mostly of basaltic composition.…”
Section: Resultsmentioning
confidence: 99%
“…It is composed nowadays of two main lakes, connected by the ephemeral Maquinchao River, partially sustained by groundwater. Fossil microbialites attest to a former higher water level in the basin [34,36]. Living and mineralizing mats were observed in 2011 in several ponds of the Maquinchao River [35].…”
Section: Introductionmentioning
confidence: 93%
“…Digital outcrop models, based on Structure from Motion techniques, were generated from photos collected systematically in terrain (see procedures in Fabuel‐Perez, Hodgetts, & Redfern, 2010 or in Bilmes et al., 2019). These digital models were used to define the geometry of strata and palaeocurrents (Duarte, Bayona, Ramírez, Baquero, & Tabares, 2019; Gómez, 2019), to add mesoscale information to the stratigraphic analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Structure-from-Motion (SfM) with Multi-View Stereo (MVS) was originally developed for the computer vision and visual perception collective and became more popular alongside the development of automatic feature matching algorithms (Spetsakis and Aloimonos, 1991;Boufama et al, 1994;Szeliski and Kang, 1994;Bilmes et al, 2019).…”
Section: Structure From Motion Photogrammetrymentioning
confidence: 99%
“…Current SfM workflows consist of automatic feature matching via the scale-invariant feature transform (SIFT) for a set of images that can be taken with different cameras from several perspectives as long as there is substantial overlap between the images (Lowe 1999;Lowe 2004;Bistacchi et al, 2015;Chesley et al, 2017;Nesbit et al, 2018;Bilmes et al, 2019). Successful triangulation of feature coordinates results in a sparse point cloud which also contains information about the camera specifications like geometry, optical information, and spatial orientation (Chesley et al, 2017;Bilmes et al, 2019). In the final stages of the workflow, a colorized dense point cloud is obtained once the tangential and spherical distortion are removed from the mathematically oriented images (Bilmes et al, 2010;Bistacchi et al, 2015;Chesley et al, 2017;Bubniak et al, 2019).…”
Section: Structure From Motion Photogrammetrymentioning
confidence: 99%